Radical Platonism in Byzantium - Niketas, Siniossoglou. (New York ; Cambridge)
xvi, 454 s.
Keywords: "Byzantium has recently attracted much attention, principally among cultural, social and economic historians. This book shifts the focus to philosophy and intellectual history, exploring the thought-world of visionary reformer Gemistos Plethon (c.1355–1452). It argues that Plethon brought to their fulfilment latent tendencies among Byzantine humanists towards a distinctive anti-Christian and pagan outlook. His magnum opus, the pagan Nomoi, was meant to provide an alternative to, and escape-route from, the disputes over the Orthodoxy of Gregory Palamas and Thomism. It was also a groundbreaking reaction to the bankruptcy of a pre-existing humanist agenda and to aborted attempts at the secularisation of the State, whose cause Plethon had himself championed in his two utopian Memoranda. Inspired by Plato, Plethon's secular utopianism and paganism emerge as the two sides of a single coin. On another level, the book challenges anti-essentialist scholarship that views paganism and Christianity as social and cultural constructions." --